Potato resistance evaluation against wart causative agent Synchytrium endobioticum (Schilbersky) Percival - Zelya, G. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. To evaluate and select breeding samples of potatoes of Ukrainian selection resistant to common and aggressive pathotypes of the cancer pathogen common in Ukraine.Methods. Over the past 11 years (2012—2023), 4219 cancer-resistant potato breeding accessions were evaluated and selected in a preliminary trial according to the guidelines modified to meet EU requirements. State testing of 163 samples was conducted. Potato samples were tested for infection with winter zoospores of the cancer pathogen using the Spiekermann A test method. Infection with summer zoospores was carried out using the Glynne-Lemmerzahl test method. To determine the resistance of potatoes to the disease, 10 tubers were planted in triplicate in the field in the foci of cancer pathotypes.Results. Out of 4219 potato breeding accessions tested during 2012—2023 in the western region of Ukraine, 3866 (91.7%) resistant and 353 susceptible potato accessions to the common pathotype (D1) of the cancer pathogen were selected in preliminary tests for resistance to cancer. State testing identified 163 breeding samples. 36 potato breeding accessions were evaluated for resistance to Ukrainian aggressive pathotypes of the pathogen.Conclusions. Resistant breeding samples against common and aggressive pathotypes of the cancer pathogen are recommended for state registration with the indication of resistance characteristics against the cancer pathogen and further zoning in the disease foci in Ukraine. Potato varieties with complex resistance to common and four local Ukrainian aggressive pathotypes of potato cancer pathogen are recommended for involvement in the breeding process as sources of resistance.